Symptom and Anxiety Assessment in Gynecologic Cancer Patients Receiving Chemotherapy - Viriyasiri, Pongsaton; Phutthikiat, Phatthanan; Phonmak, Phatthawan; Krutjaikla, Phurinut; Ongtip, Sittichai; Suprasert, Prapaporn (Asian Pacific Journal of Cancer Care, 2020)
Background: Side effects of chemotherapy usually disturbed the daily life of patients. During chemotherapy, quality of life of patients is affected by the severity of symptoms experienced. Objective: To evaluate the side effects experienced by gynecologic cancer patients receiving chemotherapy. Methods: Gynecologic cancer patients receiving chemotherapy (at least 1 cycle with standard premedication that included antiemetic drugs) between 18 June and 25 September 2019 were invited to this study. Participants were interviewed by our team for personal data and attitudes toward their disease and treatment. In addition, the Edmonton Symptom Assessment System (ESAS-Thai version) tool, and Multinational Association for Supportive Care in Cancer (MASCC) antiemetic tool were used to assess the symptoms during chemotherapy. Results: One hundred sixty-five participants entered this study. The mean age was 53.5. The three most common type of cancer were ovarian (37.6%), cervical (37.6%) and uterine cancer (21.8%). Most common chemotherapy was carboplatin plus paclitaxel (64.8%). Two-thirds of the participants believed they could be cured. The most common severe symptom from the ESAS tool was pain (20.6%), followed by fatigue (18.8%), appetite change (16.4%) and numbness (10.3%). In addition, 10.9% of patients experienced nausea/vomiting in acute phase, while 20.6% experienced it in the delayed phase. Conclusion: Our participants revealed positive attitudes toward cancer and treatment. Some patients experienced nausea and vomiting despite using antiemetic drugs. The most frequent self-reported symptom was pain. Therefore, pain control was necessary to improve their quality of life.